Root Biomass Distribution of Populus sibirica and Ulmus pumila Afforestation Stands Is Affected by Watering Regimes and Fertilization in the Mongolian Semi-arid Steppe - Nyam-Osor, Batkhuu; Byambadorj, Ser-Oddamba; Park, Byung Bae; Terzaghi, Mattia; Scippa, Gabriella Stefania; Stanturf, John A.; Chiatante, Donato; Montagnoli, Antonio (Frontiers in Plant Science, 2021)
Desertification of the semi-arid steppe of Mongolia is advancing very rapidly, motivating afforestation efforts. The “Green Belt” joint project (Government of Mongolia and Republic of Korea), which aims to mitigate soil degradation and develop agroforestry activities through the planting of a forest shelterbelt, is one such response. In these plantations, tree growth has been supported by different watering regimes (no watering, 2, 4, and 8 L h−1) and by two types of soil fertilization (NPK and Compost). The present paper analyses the effect of these techniques on soil chemistry and root biomass partitioning of Populus sibirica (Horth ex Tausch) and Ulmus pumila (L.) tree species. In July 2019, at the plantation site in Lun Soum, Tuv province (Mongolia), six trees were excavated by hand in each treatment, the root system was divided into taproot and five diameter classes (0–2; 2–5; 5–10; 10–20; > 20 mm), and the biomass was measured. Soil organic matter, macronutrients, and pH were also measured. The addition of fertilizers in the long-term did not enhance the soil chemical properties. The build-up of root biomass in both species correlated positively with increasing levels of the watering, while the application of fertilizers led to root growth suppression. For most of the root classes and both species, an irrigation level of 4 L h−1 was sufficient to yield the highest biomass and could be recommended for afforesting the semi-arid steppe of Mongolia. The root biomass of P. sibirica was more dependent on the watering regimes and of U. pumila was more negatively influenced by the application of fertilizers, indicating that U. pumila, due to the its lower water need, could be suitable for afforesting semi-arid environments. Our experiments suggest that afforestation practices in the semi-arid steppe of Mongolia should be supported by a prior analysis of plants' needs, soil type, dose, and type of fertilizers to be applied. Knowledge of the root response to the supporting techniques is necessary for choosing the best one for the plantation and, thus, to develop a sustainable and successful strategy to restore these degraded lands.